The success rate of infrazygomatic mini-implants placed with and without surgical guides: a historical control study - Lixian Yuan; Ruifeng Zhao; Jingjing Liu; Rui Tang; Shizhu Bai; Xin Liu (BMC Oral Health)
Abstract Background To improve the success rate of mini-implants, some surgical guides have been developed through digital technologies to achieve three-dimensional (3D) guided mini-implants insertion. However, there is no a surgical guide which can be applied for the insertion of infrazygomatic mini-implant. In this study, we introduced a two-trajectories surgical guide and investigated the success rate of infrazygomatic mini-implants under the guidance of the template. Methods An individualized surgical guide was fabricated based on the cone-beam computed tomography images, digital intraoral scanning images and the predesigned insertion plans. In the surgical guide group, 62 mini-implants were inserted between the maxillary first and second molars under the guidance of surgical guides (n = 62). In the historical control group, 54 mini-implants were placed by the direct manual method at the same site (n = 54). Then the mini-implant success rate in these two groups was compared. Results After implantation, 2 out of the 62 mini-implants fell off and a success rate of 96.8% was indicated in the surgical guide group. In the historical control group, 11 of 54 mini-implants fell off and the success rate was 79.6%. There was statistically significant difference between the success rate of two groups (P = 0.003). Conclusions The two-trajectories surgical guide is advantageous for the insertion of infrazygomatic mini-implant. Both the success rate and stability of infrazygomatic mini-implant were improved significantly with the use of the guide. But further studies with enlarged sample are needed to evaluate the accuracy and stability of the mini-implant placement.